The main ways and methods of the development of the information bibliographic services of the complex programs - Varnienė, Regina (Knygotyra, 1988)
The article is devoted to the problem of the information bibliographic service of complex programs. The information bibliographic experience is analyzed in this article. The author offers to develop the information bibliographic services on the basis of problem-oriented systems.